Key influencing factors of green vegetable consumption in Beijing, China. (May 2022) - Yin, Zhengqing; Li, Bo; Li, Shufei; Ding, Junqi; Zhang, Lingxian
Abstract: Green-certified vegetables are nutritious, attractive to the senses, and in line with the principles of sustainable development. The objectives of this study are to reveal the mechanism of green-certified vegetable consumption; that is, to explore the key influencing factors behind consumers' purchase intentions, purchase behavior, and willingness to pay for green-certified vegetables. Based on the Theory of Multi-attribute Attitudes and the Theory of Planned Behavior, a research framework of the consumption mechanism oriented to consumers' preferences regarding green-certified vegetable quality was established. By collecting 520 questionnaires from Beijing, China, the model was confirmed by the ordered logistic regression and interval linear regression method. The results showed that consumers have heterogeneous quality preferences, and their purchase intentions and purchase behavior levels are relatively high, with an average willingness to pay (WTP) of 138.58%. The key influencing factors driving consumers' purchase intentions, purchase behavior, and WTP include protein content belief, mineral content belief, vitamin content belief, organic vegetable safety belief, freshness belief, and taste belief. In addition, color belief and packaging quality belief significantly influenced consumers' WTP, while origin reputation belief and brand reputation belief significantly influenced consumers' purchase intention and purchase behavior. The findings of this study can guide the supply side of green-certified vegetables to improve product quality according to consumer demand, so as to promote the sustainable development of green-certified vegetables. Graphical abstract: Image 1 Highlights: Establishing a mechanism framework of green vegetable consumption behavior. Identifying the key influencing factors of green vegetable consumption. Implications of findings could guide the green vegetable industry stakeholders.